MANAJEMEN INFORMASI SPECIAL EVENT HUTTEL 62 OLEH SMA NEGERI 3 JAKARTA - Aulia, Syahidatia Chairunissa; Setianti, Yanti; Subekti, Priyo (Edulib, 2017)
The purpose of this research is to know how to process information management special event conducted by organizers HUTTEL 62 ranging from research, design, planning, coordination, and evaluation in accordance with the concept special event belongs to Joe Goldblatt. Research methods a descriptive, qualitative data with the paradigm of positivism. The results of this study suggested that the management of the special event HUTTEL 62 categorized in five stages, namely research, design, planning, coordination, and evaluation. Research carried out in the form of informal research with secondary data searches ways be monitoring news coverage about SMA Negeri 3 Jakarta. Hasl research shows the overview of the situation of informing host HUTTEL 62 is the assumption that the community name of the example contained in the SMA Negeri 3 Jakarta not sesuaid with what happened at that school. The design of the color purple and blue created the Customize the theme carried HUTTEL 62 ‘ Return Teladanku ‘. Motion design elements and sounds indicated by performers in closing. 62 HUTTEL planning begins with setting goals to be achieved, namely restoring the image of ‘ exemplary ‘ to SMA Negeri 3 Jakarta Post acts of bullying incidents. Coordination is done by the Organizer HUTTEL 62 include coordination with internal and external parties the Committee involved in organizing HUTTEL 62. The communication is done by informal meetings and mandatory meetings and communications with online messenger. The evaluation was conducted to measure the achievement of HUTTEL 62, the evaluation is conducted in the Division and the Division of any series of events have been implemented and later serve as a report on liability. Hasl acquired evaluation of barriers in the internal Committee namely the barriers of communication and information in the internal Committee. A summary of this research menenujukan that special event management HUTTEL 62 made by SMA Negeri 3 Jakarta in conveying the message of anti bully hasn’t done effectively and optimally.